A retrospective analysis of the clinicopathological and molecular characteristics of pulmonary blastoma - Zhao, Yuan-Yuan; Liu, Lin; Zhou, Ting; Zhou, Ning-Ning; Yang, Yun-Peng; Hou, Xue; Li, Yong; Zhao, Hong-Yun; Huang, Yan; Zhang, Li (OncoTargets and therapy, 2016)
The aim of this study was to analyze and summarize the clinicopathological and molecular characteristics of classic biphasic pulmonary blastoma (PB) to improve its diagnosis and treatment. A retrospective analysis was performed in patients who were diagnosed with PB at Sun Yat-Sen University Cancer Center from March 1995 to March 2015. Genomic DNA was profiled using a capture-based targeted sequencing panel. Sixteen patients with an average age of 40 years were included in this study. Accurate preoperative diagnosis was very challenging as surgically resected tissues with immunohistochemical staining were required for the diagnosis. Surgery was the optimal treatment for localized disease and there was no standard management for metastatic disease. Mutations were detected among 9 out of the 56 genes profiled, including , , , , , , , , and . Due to the low incidence rate and the reclassification of PB, no standard treatment is available. Although the numbers of cases are few with varying individual experiences, it is important to improve our understanding regarding this rare lung cancer. Targeted DNA sequencing may be of clinical use for molecular testing and the effects of targeted therapy need to be confirmed.